Lactoferrin concentration in bovine milk: validation of radial immunodiffusion technique, sources of variation, and association to udder health status - Giovanni Niero; Steffi Anna Thomas; Kassiani Mouratidou; Giulio Visentin; Massimo De Marchi; Mauro Penasa; Martino Cassandro (Italian Journal of Animal Science)
The present study aimed to evaluate analytical performances of radial immunodiffusion (RID) technique for the quantification of milk lactoferrin (LF), and to investigate the main sources of variation of LF concentration in individual milk samples of Holstein Friesian (HF, n = 1516) and Simmental (SI, n = 230) cows. Repeatability (RSDr) and reproducibility (RSDR) of RID method were assessed as relative standard deviation of 15 measurements within the same day and 45 measurements across 3 d, respectively. Sources of variation of milk LF were investigated through a mixed linear model which included the fixed effects of classes of stage of lactation and parity (and their interaction), cow breed, udder health status (UHS, based on somatic cell count and differential somatic cell count), and the random effects of the herd-test day nested within breed and the residual. Method performances were satisfactory in terms of repeatability (RSDr < 9%) and reproducibility (RSDR < 8%), suggesting that the RID can be considered as a consistent cow-side test for the quantification of milk LF. Milk LF was positively associated with somatic cell score (r = 0.40) and negatively with lactose content (r = −0.33). Lower concentration of LF was observed in milk of ‘healthy’ and ‘susceptible’ cows (13.03 and 12.87 mg/dL, respectively) compared to ‘mastitic’ and ‘chronic’ cows (17.91 and 17.33 mg/dL, respectively). In this light, milk LF has the potential to be a useful biomarker to detect early mastitis. Further research is advisable to deepen the association between milk LF content and observed clinical mastitis.Highlights Radial immunodiffusion method for milk lactoferrin quantification is repeatable and reproducible. Somatic cell count is positively associated with milk lactoferrin content. Milk lactoferrin is less concentrated in milk of healthy and susceptible than potentially mastitic and chronic cows.